2020
DOI: 10.1111/1365-2745.13406
|View full text |Cite
|
Sign up to set email alerts
|

Woody plant subregions of the Amazon forest

Abstract: 1. The Amazon forest covers 7.5 million km 2 in nine countries, hosts 25% of the global biodiversity and is a major contributor to the biogeochemical and climatic functioning of the Earth system. Despite its global importance, a regionalization of the Amazon tree flora is still lacking. Clear and data-driven delimitation of subregions is important for macroecological studies, to the identification of metacommunities and is a requisite for conservation planning. 2. We aimed at identifying and mapping plant spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 118 publications
1
14
1
Order By: Relevance
“…In contrast, the other seven vegetation types have a low proportion of species restricted to them, ranging from 6% in coastal mosaics and savanna s.s. to 25% in tepuis. Species shared between terra Moreover, because these edaphic gradients are consistently important in segregating Amazonian vegetation types from local to continental scales, our results run counter to previous findings which have suggested that tree community composition in the Amazon is primarily driven by Amazon-wide gradients in environmental conditions (e.g., precipitation seasonality, soil fertility; Silva-Souza & Souza, 2020;ter Steege et al, 2006). Previous Amazon-wide studies analyzed tree species composition data without separating or considering the different Amazonian vegetation types.…”
Section: Re Sultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, the other seven vegetation types have a low proportion of species restricted to them, ranging from 6% in coastal mosaics and savanna s.s. to 25% in tepuis. Species shared between terra Moreover, because these edaphic gradients are consistently important in segregating Amazonian vegetation types from local to continental scales, our results run counter to previous findings which have suggested that tree community composition in the Amazon is primarily driven by Amazon-wide gradients in environmental conditions (e.g., precipitation seasonality, soil fertility; Silva-Souza & Souza, 2020;ter Steege et al, 2006). Previous Amazon-wide studies analyzed tree species composition data without separating or considering the different Amazonian vegetation types.…”
Section: Re Sultscontrasting
confidence: 99%
“…Previous Amazon-wide studies analyzed tree species composition data without separating or considering the different Amazonian vegetation types. If composition is summarized within geographic grid cells (e.g., Silva-Souza & Souza, 2020;ter Steege et al, 2006), then a given grid cell may take on Values under NMDS1 and NMDS2 represent the coefficients of determination (adjusted R 2 , and their respective p-values) of generalized linear models (GLMs) between the first two axes of a non-metric multidimensional scaling and environmental variables. Values in the last row represent coefficients of determination of GLM-based multiple regressions between each NMDS axis and all significant variables.…”
Section: Re Sultsmentioning
confidence: 99%
“…The CWM traits of specific leaf area (mm 2 mg -1 ), leaf dry matter content (g g -1 ), leaf nitrogen content (mg g -1 ), leaf thickness (mm), wood density (g cm -3 ), seed dry mass (mg) and maximum plant height (m) were computed based on abundance data regarding 2122 species distributed across 281 local communities. Community data were compiled from bibliographic sources and organized into the Caaporã database, which has been used in a number of recent publications on macroecological patterns of Brazilian and South American biomes (Cantidio & Souza 2019, Silva-Souza & Souza 2020, Silva et al 2021b. Further details on the use of this database in the Atlantic Forest can be found in Cantidio and Souza (2019) and Silva et al (2021b).…”
Section: Functional Trait Datamentioning
confidence: 99%
“…The ISODATA algorithm works by clustering n groups of pixels with similar spectral characteristics in the input bands from two until the maximum number of clusters is reached in order to find the best solution for the clusters (Memarsadeghi et al 2007). This requires the suggestion of an initial maximum number of clusters, which was determined using the L-method with 1000 iterations (Salvador & Chan 2004) following previous studies (Moura et al 2016, Cantidio & Souza 2019, Silva-Souza & Souza 2020. The L-method is a Euclidean-based procedure running piecewise regressions on repeated k-means partitions applied on a dissimilarity matrix of CWM traits (Salvador & Chan 2004).…”
Section: Data Analysesmentioning
confidence: 99%
“…The study areas are distant from each other by 120 and 230 km, respectively, and were all originally covered by the same type of tropical rainforest (Xingu/Tocantins/Araguaia and Tocantins/Pindare moist forests; Silva-Souza & Souza, 2020) within the Belém centre of endemism (Cardoso Da Silva et al, 2005).…”
Section: Introductionmentioning
confidence: 99%